Autoimmune channelopathies: well-established and emerging immunotherapy-responsive diseases of the peripheral and central nervous systems. - Vincent, A (2010)
BACKGROUND: The role of antibodies in neuromuscular junction disorders is well established with antibodies to acetylcholine receptor, muscle-specific kinase, and voltage-gated calcium channels. The diseases associated with these antibodies, myasthenia gravis and the Lambert-Eaton myasthenic syndrome, respond well to symptomatic treatments (e.g., cholinesterase inhibitors) and to immunotherapies such as plasma exchange, intravenous immunoglobulin, oral steroids, and steroid-sparing drugs. The role of the antibodies has been established by a variety of in vitro and in vivo approaches. More recently, antibodies to voltage-gated potassium channels have been identified in patients with autoimmune forms of acquired neuromyotonia. Over the last decade, antibodies to CNS membrane receptors or ion channels have begun to be identified and these antibodies define antibody-mediated CNS diseases that also respond to immunotherapies. SUMMARY: The paradigms gained from the study of the peripheral conditions has led to a better appreciation of the role of antibodies in neurological disorders and a growing recognition of their role in central nervous system (CNS) diseases.